The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5539/elt.v8n12p182
|View full text |Cite
|
Sign up to set email alerts
|

Choosing an English Teacher: The Influence of Gender on the Students’ Choice of Language Teachers

Abstract: Gender and teaching are gaining increasing attention in the field of higher education. The significance of teacher gender seems even more crucial in an environment based on gender segregation. In the scope of language teaching and gender, this study investigates the influence of gender on the students' selection of teachers in general, and language teachers more specifically. The participants, 146 English major students in an all-female college of education, were given a questionnaire of 32 statements--to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Because classes in the Middle East can be segregated, it is understandable (though clearly not acceptable) that the teacher should be of the same gender, but in Colombia, the request for a female teacher is harder to fathom. This finding also contradicts research in other contexts that suggests a preference for male teachers in the profession (e.g., Amin, 2001; Kobayashi, 2014; Taqi, Al‐Darwish, Akbar, & Al‐Gharabali, 2015). One possible explanation, which is suggested by three of the ads, is that female teachers are required for private classes with female students or for positions in all‐girls schools.…”
Section: Findings and Discussioncontrasting
confidence: 93%
“…Because classes in the Middle East can be segregated, it is understandable (though clearly not acceptable) that the teacher should be of the same gender, but in Colombia, the request for a female teacher is harder to fathom. This finding also contradicts research in other contexts that suggests a preference for male teachers in the profession (e.g., Amin, 2001; Kobayashi, 2014; Taqi, Al‐Darwish, Akbar, & Al‐Gharabali, 2015). One possible explanation, which is suggested by three of the ads, is that female teachers are required for private classes with female students or for positions in all‐girls schools.…”
Section: Findings and Discussioncontrasting
confidence: 93%
“…Research on effective EFL teachers has revealed a number of qualities that contribute to students’ language learning success. These qualities have mostly revolved around a number of categories: personality, language knowledge, teaching methods, organization and communication skills, and socioaffective skills (Abu-Rahmah, 2008; Al-Mahrooqi et al, 2015; Baytur & Razi, 2015; Brosh, 1996; Febriyanti, 2018; Gabrielatos, 2002; Park & Lee, 2006; Salahshour & Hajizadeh, 2013; Taqi et al, 2015; Wichadee, 2010). In addition, having reviewed literature on the effectiveness of EFL teachers, Al-Seghayer (2017) summarized those qualities into five main categories: cognitive knowledge, content knowledge, language proficiency, personality traits, and other related key variables that can be achieved through a number of channels, including initiatives and training programs and support and professional development opportunities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The gender has been correlated with students’ and teachers’ choices of EFL teacher effectiveness and various findings have been revealed. Some studies reported differences in the choices of respondents attributed to genders (Abu-Rahmah, 2008; Chen & Lin, 2009; Ramazani, 2014; Taqi et al, 2015). However, some other studies showed that the genders did not have any effect on the respondents’ choices regarding the qualities of effective EFL teacher (Nghia, 2015; Wichadee, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hedges can be depicted for a range of positive functions: 1) expressing shades of confidence or doubt, 2) allowing women to be sensitive to others' feelings, 3) assisting women in the search for the right words to express what they mean, and 4) allowing women to avoild playing the expert status. Taqi et al (2015) argue that, in the last the last two decades, it has seen various modern and somewhat conflicting theories with regards to learners' gender dynamics in the classroom and its effects on teaching and learning. The patterns of gender are an affective part of the educational construction due to the fact that gender has always been associated with language teaching and learning (Appleby, 2014).…”
Section: )mentioning
confidence: 99%